MEANING OF TRADITION MANITI ANAK IN THE MARRIAGE CEREMONY (Studi Kasus : Country Kinali, Subdistrict Kinali District Pasaman Barat) - Asri, Kurniati; Maihasni, Maihasni; Firdaus, Firdaus (Pendidikan Sosiologi, 2013)
Indigenous traditions carried out with reference to the tradition of the ancestors who have traditional values that can later be used as a sociocultural ethnic a region, associated with the ground realities in mind that the maniti anak tradition in terms of its implementation requires considerable cost and work fairly complicated but until now this tradition is still carried out by the villagers Kinali. This study aims to describe the implementation process of the maniti anak tradition in marriage ceremonies and describe the meaning of tradition maniti anak in the marriage ceremony. This type of research is descriptive qualitative research. Selection of informants using purposive sampling technique. Type of data used is primary data. Methods of data collection is done in two ways: observation and interviews. Analysis of the data used by the model of interactive data analysis (Milles and Huberman) which includes the four stages, namely: (1) data collection phase, (2) data reduction phas, (3) data presentation stage and (4) the conclusion stage. It can be concluded that maniti anak have stages that do like capturing the mancari dana, bakumpua dirumah bako, bagalombang, panyarahan pambarian bako and ends with baretong. Of tradition maniti anak , there is meaning contained therein such pride in themselves bako and strengthen family relationships.